Bagasse as a carbon structure with high sulfur content for lithium–sulfur batteries. Issue 54 (1st September 2020) - Ma, Jingjing; Yang, Li; Yang, Xiaoxun; Li, Yuanchao; Zhao, Erqing; Fan, Shumin; Xu, Guangri; Lou, Tianjun; Niu, Hongying
Abstract : Bagasse-based carbon matrix with microporous structure and nitrogenous functional groups could have high sulfur loading and excellent polysulfide absorption capacity. Abstract : A bagasse-based 3D carbon matrix (BC) with high specific surface area and high conductivity was obtained by carbonization and pore-forming processes with bagasse as the carbon precursor and K2 FeO4 as the pore-former. The microporous structure and nitrogenous functional groups were determined in the prepared carbon matrix, which could allow high sulfur loading and improve the polysulfide absorption capacity during cycling. After sulfur infusion, the S/BC composite with 68.8% sulfur content was obtained. The lithium–sulfur (Li–S) battery with the S/BC cathode shows high specific capacity and good cycling performance. It delivers a specific capacity of 1360 mA h g −1 at 0.2C and remains at 790 mA h g −1 after 200 cycles. At 1C, the Li–S with this composite cathode exhibits 601 mA h g −1 after 150 cycles. This work offers a new kind of green material and a new method for Li–S batteries.